Effect of Rifabutin on the Pharmacokinetics of Oral Cabotegravir in Healthy Subjects. Issue 4 (May 2019) - Ford, Susan L; Lou, Yu; Lewis, Nicole; Kostapanos, Michalis; D'Amico, Ronald; Spreen, William; Patel, Parul
Background: Cabotegravir (CAB) is an integrase strand transfer inhibitor in development as a long-acting injectable formulation, with an oral formulation used during a safety lead-in period. Tuberculosis (TB)–HIV coinfection is common, often requiring simultaneous treatment. Rifabutin (RBT) is an alternative antimycobacterial agent for TB and a moderate inducer of cytochrome P450 and UDP-glucuronosyltransferase isoenzymes. This study evaluated the impact of RBT on the pharmacokinetics (PK) of oral CAB. Methods: In this Phase I, single-centre, open-label, two-period, fixed-sequence, drug interaction study, subjects received oral CAB 30 mg once daily for 14 days in period 1, and oral CAB plus RBT 300 mg once daily for 14 days in period 2. Serial PK sampling was performed on days 14 and 28. Geometric least squares (GLS) mean ratios with associated 90% CIs were calculated to compare CAB non-compartmental PK parameters following CAB+RBT versus CAB alone. Safety was also assessed. Results: A total of 15 male subjects were enrolled and 12 completed all treatments. Comparing CAB+RBT with CAB alone, the GLS mean ratios (90% CIs) for CAB area under the concentration–time curve from time zero to the end of the dosing interval (AUC0–τ ), maximum observed plasma concentration (Cmax ) and concentration at the end of the dosing interval (Cτ ) were 0.79 (0.74, 0.83), 0.83 (0.76, 0.90) and 0.74 (0.70, 0.78), respectively. 11 subjects reported 24 adverse events (AEs); 22 were reported with CAB+RBT (3 drug-related) and 2 with CAB alone (not drug-related). All AEs resolved by study end. Conclusions: RBT had a modest impact on plasma CAB exposure following oral coadministration, resulting in overall plasma CAB trough exposures above the 10 mg oral dose shown to maintain viral suppression in HIV-1-infected subjects. Oral CAB can be coadministered with RBT without dosage adjustment.